2014
DOI: 10.1007/s11547-014-0434-8
|View full text |Cite
|
Sign up to set email alerts
|

Contrast-enhanced MR angiography: does a higher relaxivity MR contrast agent permit a reduction of the dose administered for routine vascular imaging applications?

Abstract: Under identical examination conditions a single 0.1 mmol/kg body weight dose of gadobenate dimeglumine can fully replace a double 0.2 mmol/kg body weight dose of gadopentetate dimeglumine for routine CE-MRA procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
1
4
0
Order By: Relevance
“…In particular, at increasing magnetic field strengths gadolinium R1 relaxivity tends to decrease, hence one might expect a parallel deterioration of image contrast in MRA; however, the increased SNR achieved at higher magnetic field, as well as the improved background suppression due to the higher T1 of extravascular tissues, leads to an overall increase of vascular enhancement after contrast agent injection [22]. Even if the relaxivity of both Gadoteridol and Gadobutrol is negatively affected by the increased field strength, the resulting difference remains similar to what has been reported at 1.5T, with a difference that is not sufficient to significantly influence intravascular enhancement and SNR [6,23,24]. The implications of this study for routine practice may be relevant in terms of cost and convenience, since Gadoteridol is less expensive (around 80 euros per single dose vial) in comparison with Gadobutrol (around 130 euros per single dose vial).…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…In particular, at increasing magnetic field strengths gadolinium R1 relaxivity tends to decrease, hence one might expect a parallel deterioration of image contrast in MRA; however, the increased SNR achieved at higher magnetic field, as well as the improved background suppression due to the higher T1 of extravascular tissues, leads to an overall increase of vascular enhancement after contrast agent injection [22]. Even if the relaxivity of both Gadoteridol and Gadobutrol is negatively affected by the increased field strength, the resulting difference remains similar to what has been reported at 1.5T, with a difference that is not sufficient to significantly influence intravascular enhancement and SNR [6,23,24]. The implications of this study for routine practice may be relevant in terms of cost and convenience, since Gadoteridol is less expensive (around 80 euros per single dose vial) in comparison with Gadobutrol (around 130 euros per single dose vial).…”
Section: Discussionsupporting
confidence: 67%
“…18 carotid arteries were evaluated in the 9 patients in group A (Gadobutrol-enhanced MRA) and 42 carotid arteries were evaluated in the 21 patients in group B (Gadoteridol-enhanced MRA) ( Table 1). The average contrast agent volume administered was 7.3 ± 1.2 ml [6][7][8][9][10] in group A and 14 ± 1.9 ml [11][12][13][14][15][16][17][18] (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that a single Gd‐BOPTA dose can replace a double Gd‐DTPA dose for several MR applications. Gd‐BOPTA yielded qualitatively and quantitatively comparable diagnostic results compared with full‐dose Gd‐DTPA in several previous studies of the brain, heart, and vascular system …”
Section: Discussionmentioning
confidence: 99%
“…In this context, preference to macrocyclic GBCAs and strategies to reduce the injected dose of Gd as far as possible while maintaining good diagnostic performance in CE-MRA have been considered 10 . This can also be facilitated by the use of high-relaxivity MR contrast agents (CAs) 11 . Gadopiclenol, a macrocyclic GBCA, has a 2- to 3-fold higher T1 relaxivity than the marketed GBCAs, maintained at very high field 12 .…”
mentioning
confidence: 99%